Review of Kenneth Cauthen's Process ethics: a constructive system - Rolston, Holmes, 1932-2025, author; Joint Publication Board of Zygon, publisher (Colorado State University. Libraries, 1986)
This is a process oriented theology, blending Christian ethics based on the Bible and moral philosophy based on reason and experience. He synthesizes rights-based and utilitarian ethics, agape and eros, love and justice, individual and community, Christian ethics and evolutionary processes, self-love and altruism.
Process ethics: a constructive system - review
This is an electronic version of an article published in Zygon®: Journal of Religion and Science.
Keywords: process philosophy; Bible and reason; rights; utility; justice; community; self-love; altruism; Christian ethics